Fasies gunungapi, dan evolusi magmatik berdasarkan analisis geokimia Kompleks Todoko-Ranu, Kecamatan Sahu, Halmahera, Maluku Utara - Kusumayudha, Sari Bahagiarti; Laratmase, Lotong; harjanto, Agus (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
The Todoko-Ranu volcanic complex is situated in the Sahu District, West Halmahera Regency, North Maluku. Geomorphologically, this area shows various volcanic landforms, reflecting the development and changes in the characteristics of eruptive activities. Eruption characteristic of a volcano is influenced by the physical and chemical properties of magma. Todoko-Ranu volcanic complex was built by volcanic products, including lava deposits, pyroclastic deposits and lahar deposits, which have different geochemical compositions. Due to the variety compositions of rocks, it is important to carry out studies on magmatic evolution based on geochemical analysis in the area. This study is useful for knowing the characteristics of the eruption at that time. Thus, the aim of this research is to study and analyze the geochemistry of volcanic rocks in order to determine the magmatic evolution of the Todoko-Ranu volcanic complex. The method applied is mapping the distribution of rocks and geological structures, testing rock samples for petrographic analysis and geochemical analysis, then studying magmatic processes. The results of the study show that the volcanic rocks of the Todoko-Ranu complex originate from calc-alcaline and tholeiitic magma which was formed from oceanic plate partial melting in a convergent tectonic environment, then underwent an evolution from alkaline to more acidic due to the process of magma differentiation and assimilation.